Integrating the 40 acres : the fifty-year struggle for racial equality at the University of Texas - Goldstone, Dwonna Naomi, 1968- (University of Georgia Press, 2006)
"In this first full-length history of the university's desegregation, Dwonna Goldstone examines how, for decades, administrators only gradually undid the most visible signs of formal segregation while preventing true racial integration." "Goldstone's coverage ranges from the 1950 U.S. Supreme Court ruling that the University of Texas School of Law had to admit Heman Sweatt, an African American, through the 1994 Hopwood v. Texas decision, which ended affirmative action in the state's public institutions of higher education. She draws on oral histories, university documents, and newspaper accounts to detail how the university moved from open discrimination to foot-dragging acceptance to mixed successes in the integration of athletics, classrooms, dormitories, extracurricular activities, and student recruitment. Goldstone incorporates not only the perspectives of university administrators, students, alumni, and donors, but also voices from all sides of the local and national civil rights movement."--Jacket